Goethe's Faust and cultural memory : comparatist interfaces - Fitzsimmons, Lorna, 1957- (Lehigh University Press, 2012)
This book is an interdisciplinary collection of essays examining Goethe's Faust and its derivatives in European, North American, and South American cultural contexts. Topics include the authority of the word in Faust and Dr. Faustus, cultural memory of Herder, the Eternal-Feminine, Coleridge's responses to Faust.